A near infrared spectral sequence of O-type dwarfs - Giudici Michilini, Federico Nicolás (2023)
The study of spectral morphology is a powerful tool for understanding the fundamental properties of stars. The spectral classification scheme for O stars has been revised in the context of the Galactic O-Star Spectroscopic Survey and a new set of spectral standard stars was proposed. Since the vast majority of the Galactic O stars are visible only in the infrared as they are subject to large interstellar absorption in the optical, it is necessary to extend this work towards those wavelengths. We are working on the construction of a spectral atlas with high quality observations between 0.85 μm and 2.5 μm. The first observations for this project date back to 2013 and were made with the GNIRS (Gemini Observatory, Hawaii) and FIRE (Las Campanas Observatory, Chile) spectrographs. We present here a new batch of results, which includes spectra of a sequence of dwarf standard stars with spectral types ranging from O4 to B0 in the X, Y, J, H, and K near-infrared bands. We analyze this data set to establish some spectral characteristics of such stars, with the aim of defining classification criteria in the near-infrared range such as the ratios between He I λ1.700 μm and HeII λ1.042 μm and between He I λ1.700 μm and HeII λ1.692 μm.